Analisis Finansial Usaha Pemanfaatan Limbah Ternak Sapi Sebagai Bahan Baku Biogas - Halimah, Andi Sitti (Universitas Galuh, 2024)
The development of information and knowledge has slowly led the community, especially breeders, to utilize cattle waste, which initially had a negative impact on the environment, to become an alternative energy source or biogas to become a natural fertilizer for plants. This study aims to analyze the financial feasibility of the business of utilizing cattle waste to become biogas feedstock. By using some quantitative data to support the calculation of the financial aspect, the results of the feasibility analysis based on the eligibility criteria used, obtained an NPV value of Rp. NPV IDR 185,127,000 IRR 43.25% and B/C ratio 1.69. These values indicate if the business on both installations at the site is declared feasible for development.